Chamuangone-enriched rice bran oil ameliorates neurodegeneration in haloperidol-induced Parkinsonian rat model via modulation of neuro-inflammatory mediators and suppression of oxidative stress markers - S. Alotaibi, Badriyah; Saleem, Uzma; Ahmad, Aqsa; Chaudhary, Zunera; Farrukh, Maryam; O. Khayat, Rana; Alsharif, Ifat; A. S. Baokbah, Tourki; Albalawi, Aishah E.; A. Althobaiti, Norah; Ajmal Shah, Muhammad; Anam, Khairul; et al. (Italian Journal of Food Science, 2024)
A natural bioactive compound chamuangone extracted from Thai salad Garcinia cowa leaves exhibited robust medicinal properties, targeting central oxidative stress pathways, and having neuroprotective potential. Chamuangone-enriched rice bran oil (CERBO), with 1.97 mg/mL chamuangone, was obtained through green extraction. The study was designed to evaluate the anti-Parkinson’s activity of CERBO in the haloperidol- induced Parkinsonian rat model. Animals were categorized into six groups as control, disease control and treatment groups. Parkinson’s disease (PD)-like symptoms were induced by administration of haloperidol 1 mg/kg, intraperitoneally; CERBO treatment groups received 2.5, 5, and 7.5 mg/kg orally before the administration of haloperidol for 21 days. Neurobehavioral, biochemical, neurochemical, and histopathological studies along with gene expression analysis were performed at the completion of the study. CERBO markedly recover the motor and non-motor PD-like symptoms in treatment groups dose-dependently. The levels of antioxidant enzymes, such as catalase, superoxide dismutase, reduced glutathione, and glutathione peroxidase, increased, while malondialdehyde levels decreased dose-dependently in CERBO-treated groups. CERBO dose-dependent elevations were observed in neurotransmitters (dopamine, serotonin, and noradrenaline). PD-associated specific biomarker (α-synuclein) decreased dose-dependently with downregulation in messenger RNA expression of neuro-inflammatory mediators (interleukin α, interleukin 1β, and tumor necrosis factor-α). Histopathological studies revealed recovery in neuronal loss, formation of Lewy’s bodies, and neurofibrillary tangles in the treatment groups. It was concluded from the data that CERBO possessed good anti-Parkinson’s activity and could be a novel, safe, and effective remedy for the treatment of PD.